Patient-Specific Stent Fabrication Using a Seven-Degree-of-Freedom Additive Manufacturing System - John M. Huss; Malachi Lehman; Arthur G. Erdman (Machines, 2022)
With advances in additive manufacturing technologies, the creation of medical devices which are tailored to the geometry of a patient’s unique anatomy is becoming more feasible. The following paper details the capabilities of a seven-degree-of-freedom fused filament deposition modeling system which enables a wide variety of user-control over previously restricted parameters, such as nozzle angle, print bed rotation, and print bed tilt. The unique capabilities of this system will be showcased through the production of a patient-specific tracheal stent using three different methods: segmented overmolding, transverse rastering, and longitudinal rastering. The resulting opportunities and time savings demonstrated by the prints will provide a case for greater implementation of seven-degree-of-freedom manufacturing technologies.